Leukemia-associated truncation of granulocyte colony-stimulating factor receptor impacts granulopoiesis throughout the life-course - Bulleeraz, Vilasha; Goy, Michelle; Basheer, Faiza; Liongue, Clifford; Ward, Alister C. (Frontiers in Immunology, 2023)
Introduction The granulocyte colony-stimulating factor receptor (G-CSFR), encoded by the CSF3R gene, is involved in the production and function of neutrophilic granulocytes. Somatic mutations in CSF3R leading to truncated G-CSFR forms are observed in acute myeloid leukemia (AML), particularly those subsequent to severe chronic neutropenia (SCN), as well as in a subset of patients with other leukemias. Methods This investigation introduced equivalent mutations into the zebrafish csf3r gene via genome editing and used a range of molecular and cellular techniques to understand the impact of these mutations on immune cells across the lifespan. Results Zebrafish harboring truncated G-CSFRs showed significantly enhanced neutrophil production throughout successive waves of embryonic hematopoiesis and a neutrophil maturation defect in adults, with the mutations acting in a partially dominant manner. Discussion This study has elucidated new insights into the impact of G-CSFR truncations throughout the life-course and created a bone fide zebrafish model for further investigation.